Given the equation:

tan 3x - 2tan^3 x = 0

We need to find x values.

==> tan 3x = 2tan^3 x

Now from trigonometric identities we know that:

tan 3x = (3tan x - tan^3 x)/ (1-3 tan^2 x)

Let us substitute:

==> (3tan x - tan^3 x) /...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Given the equation:

tan 3x - 2tan^3 x = 0

We need to find x values.

==> tan 3x = 2tan^3 x

Now from trigonometric identities we know that:

tan 3x = (3tan x - tan^3 x)/ (1-3 tan^2 x)

Let us substitute:

==> (3tan x - tan^3 x) / (1-3tan^2 x) = 2tan^3 x

Now we will multiply by 1-3tan^2 x

==> 3tanx - tan^3 x = 2tan^3 x ( 1- 3tan^2 x)

==> 3tanx - tan^3 x = 2tan^3 x - 6tan^5 x

==> 6tan^5x - 3tan^3 x + 3tanx = 0

==> 3tanx(2tan^4 x - tan^2 x+1) = 0

==> Let u = tan^2 x

==> 3tanx ( 2u^2 - u +1) =0

But the equation between the brackets has no real solution.

Then the only solution is:

**tanx = 0 ==> x = 0, pi, 2pi **

**==> x = n*pi where n = 0, 1, 2, ....**